2020
DOI: 10.1007/s00122-020-03686-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and cross-validation of genetic loci conferring resistance to Septoria nodorum blotch using a German multi-founder winter wheat population

Abstract: Key message We identified allelic variation at two major loci, QSnb.nmbu-2A.1 and QSnb.nmbu-5A.1, showing consistent and additive effects on SNB field resistance. Validation of QSnb.nmbu-2A.1 across genetic backgrounds further highlights its usefulness for marker-assisted selection. Abstract Septoria nodorum blotch (SNB) is a disease of wheat (Triticum aestivum and T. durum) caused by the necrotrophic fungal pathogen Parastagonospora nodorum. SNB resistance is a typical quantitative trait, controlled by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…We identified one QTL ( QSnb.sdsu-2D ) on the short arm of chromosome 2D, which physically maps to 9 Mb on the wheat reference genome. Two recent studies 53 , 54 have also reported SNB resistance QTLs in the same region (~ 14–15 Mb) at the adult plant stage. This region also harbors the SnTox2 sensitivity gene Snn2 (6–12 Mb) 53 ; thus, QSnb.sdsu-2D identified in this study co-locates with this sensitivity gene.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…We identified one QTL ( QSnb.sdsu-2D ) on the short arm of chromosome 2D, which physically maps to 9 Mb on the wheat reference genome. Two recent studies 53 , 54 have also reported SNB resistance QTLs in the same region (~ 14–15 Mb) at the adult plant stage. This region also harbors the SnTox2 sensitivity gene Snn2 (6–12 Mb) 53 ; thus, QSnb.sdsu-2D identified in this study co-locates with this sensitivity gene.…”
Section: Discussionmentioning
confidence: 78%
“…The current study also validated another genomic region on chromosome 2AL at ~ 780 Mb. Several studies have identified loci for seedling and adult plant resistance in the same region 20 , 47 , 53 , 54 . In a very recent report, Lin et al 53 identified an adult plant resistance QTL in the same region positioned between 755 and 780 Mb, overlapping with the QSnb.sdsu.2A .…”
Section: Discussionmentioning
confidence: 99%
“…The physical interval for Qsnb.cur–2AS1 is notably large (22). Nevertheless, several recent studies suggest the locus contains a gene conferring sensitivity to an undiscovered NE, that functions as an important determinant of both seedling, adult leaf and glume SNB resistance since these QTL overlap with Qsnb.cur–2AS1 (20, 22, 26, 54). In addition, a minor seedling resistance QTL on chromosome 2A was detected in a recombinant inbred population derived from Swiss winter wheat varieties Arina and Forno (20).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tan et al (8) demonstrated that the deletion of ToxA, Tox1 and Tox3 in P. nodorum SN15 did not significantly alter virulence on a diverse collection of modern wheat varieties (8,9). A further complication in breeding for SNB resistance is that some NE-host gene interactions were not consistently detected in field trials using mapping populations with known susceptibility genes (25,26). It is intuitive to hypothesise that NE epistasis plays a significant role in shaping the variations observed in host resistance to SNB (Table 1) (27).…”
Section: Introductionmentioning
confidence: 99%
“…nodorum SN15 did not significantly alter virulence on a diverse collection of modern wheat varieties [ 8 , 9 ]. A further complication in breeding for SNB resistance is that some NE-host gene interactions were not consistently detected in field trials using mapping populations with known susceptibility genes [ 25 , 26 ]. It is intuitive to hypothesise that NE epistasis plays a significant role in shaping the variations observed in host resistance to SNB ( Table 1 ) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%